دور الابداع التقني في تحقيق جودة الخدمات الفندقية: دراسة تطبيقية لآراء عينة من العاملين الاداريين في عدد من المنظمات الفندقية في محافظة اربيل - حسن عودة غضاب (PROSPECTIVE RESEARCHES, 2023)
Adopting technical creativity by organizations represents best choices of adapting with fast changes in the environment of working hotel according to its own approach and its future view. Thus, the research seeks for achieving a set of goals represented by assessing technical creativity and its impact in providing products according to the changing customer desires. The research also deals with the impact of technical creativity in the product design. In the light of this, the research sheds light on the role of technical creativity in achieving the quality of hotel services which is an analytical study for a sample of guests in many hotel organizations in Irbil city. The conclusions and suggestions of this paper are the necessity of relying on technical creativity in designing and improving the new products. The technical productivity is a means by which the organizations can compete with others and even being superior on them, as well as their ability on providing the products to fulfill the changing needs and desires of the customers. The research includes the theoretical and practical parts and the relationship between them. The research includes the following: 1.Research methodology. 2.A conceptual framework for (technical creativity). 3.A conceptual framework for the quality of hotel services. 4.The practical aspect. 5. Conclusions and suggestions.